* Age should not be a barrier to performing capsule endoscopy in the elderly with anaemia. (13th March 2011) - Sidhu, R; Muhammad, I; McAlindon, M E
Abstract : Introduction: Capsule endoscopy (CE) has developed an important role in the investigation of patients with obscure gastrointestinal bleeding (OGB). There is paucity in the published literature on the use of CE in OGB in the elderly. We conducted a study to investigate the utility of CE in the elderly with recurrent anaemia ± overt bleeding and impact on subsequent management compared to the younger cohort. Methods: A retrospective review of consecutive patients that underwent CE over a seven year period (2002–2009) for OGB was conducted. Data was collected on demographics, CE findings and subsequent change in management for patients in group 1(≤70 years) and group 2 (<70 years). Results: 779 patients underwent CE for OGB in the time period. Thirty five percent of patients (n=272) were ≤70 years (group 1) with a median age of 76 years (range 70–92 years). The majority of patients in group 1 underwent CE for the indication of recurrent anaemia (n=200) while overt bleeding consisted of 27% (n=72). The diagnostic yield of CE in group 1 was 53%. There was no significant difference in the yield between those with anaemia or overt bleeding (52% versus 58%, p=0.3). The commonest diagnosis in the elderly was angioectasia in 34% of patients. The other findings included small bowel carcinoid tumours (n=2), Crohn's disease (n=2), fresh bleeding in the small bowel (n=8) small bowel diverticulae (n=2), small bowel ulcers (n=18) and miscellaneous (n=8). In 8% of patients, pathology was found outside the small bowel. In 5 patients, pathology were found in the caecum which included caecal angiodysplasia (n=3), ulcers (n=1) and a colonic tumour (n=1) while pathology in the upper gastrointestinal tract consisted of 6%. Of these gastric antral vascular ectasia was seen in eight patients that had been misdiagnosed as gastritis. On logistic regression, factors which predicted a higher yield with CE included age (p=0.03), anticoagulation (p=0.045) and previous blood transfusions (p=0.04). Management was altered in 33% in the form of enteroscopy ± APC or polypectomy, repeating colonoscopy, surgery for resection of tumour or sewing of angiomata and treatment of peptic ulcer disease. In comparison to patients < 70 years, the diagnostic yield was significantly higher in the elderly for both the indication of anaemia (51% vs 37%, p=0.003, OR 1.8, 95% CI 1.3 to 2.5) and OB (60% versus 40%, p=0.007, OR 2, CI 1.2 to 3.9). Management was also altered in a significant greater proportion of the elderly (p=0.002, OR 1.8, CI 1.3 to 2.5). Conclusion: CE has a high diagnostic yield and positive impact on management in patients > 70 years. Age should not be a barrier to performing CE in the elderly.